2020
DOI: 10.1016/j.bja.2019.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological and clinical considerations in the perioperative care of patients with a previous ischaemic stroke: a multidisciplinary narrative review

Abstract: With an ageing population and increasing incidence of cerebrovascular disease, an increasing number of patients presenting for routine and emergency surgery have a prior history of stroke. This presents a challenge for pre-, intra-, and postoperative management as the neurological risk is considerably higher. Evidence is lacking around anaesthetic practice for patients with vascular neurological vulnerability. Through understanding the pathophysiological changes that occur after stroke, insight into the suscep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 157 publications
0
33
0
2
Order By: Relevance
“…2020 a ), there are no available prospective studies on the use of NaHCO 3 – to generate an equivalent effect in acute ischaemic stroke patients (Minhas et al . 2020 b ).…”
Section: Discussionmentioning
confidence: 98%
“…2020 a ), there are no available prospective studies on the use of NaHCO 3 – to generate an equivalent effect in acute ischaemic stroke patients (Minhas et al . 2020 b ).…”
Section: Discussionmentioning
confidence: 98%
“…The temporal changes in the end-tidal CO 2 demonstrated in this study highlight the importance of monitoring this variable in large vessel occlusion ischemic stroke patients, especially in the immediate peri-procedural and post-procedural period, given its known effect on cerebral blood flow [18,19]. The higher end-tidal CO 2 levels in patients with incomplete recanalization, especially at later time points, is intriguing and may reflect higher infarct volumes, which this variable (end-tidal CO 2 ) was shown to be associated with.…”
Section: Discussionmentioning
confidence: 78%
“…End-tidal carbon dioxide is also an important, potentially modifiable factor that influences cerebral blood flow, where hypocapnia is known to occur frequently in acute ischemic stroke patients [18]. This in addition to other peri-procedural factors, including the mode of anesthesia, which may have a profound impact on patient outcomes through modifying cerebral blood flow and autoregulation [19]. Thus, a more complete understanding and quantification of the autoregulatory profile of patients post EVT may help to determine which patients are at the highest risk of a reperfusion injury and/or an infarct expansion ischemia, which can be used to guide both intraoperative and post-procedural hemodynamic management.…”
Section: Introductionmentioning
confidence: 99%
“…Coverdale et al (2014) have shown that the cross-sectional area of the MCA can change under extreme hypercapnic and hypocapnic conditions, but these extremes were not observed in our study [ 42 ]. Additionally, CBFV could be influenced by several factors including ICP, haematocrit and carbon dioxide levels, which were not adjusted for within this analysis [ 43 ]. Therefore, during these conditions the CBFV may not accurately represent the CBF.…”
Section: Discussionmentioning
confidence: 99%